The Impact of CSR on Rural Women Custodians of Seed, Food and Climate Change Resilience in Nigeria's Niger Delta Region - Joseph I. Uduji; Elda N. Okolo-Obasi (African Governance and Development Institute (AGDI), 2023)
Purpose - The purpose of this paper is to critically examine the multinational oil companies' (MOCs) corporate social responsibility (CSR) initiatives in Nigeria. Its special focus is to investigate the impact of the global memorandum of understanding (GMoU) on development of enterprising rural women as custodians of seed, food and traditional knowledge for climate change resilience in the Niger Delta region of Nigeria. Design/methodology/approach - This paper adopts a survey research technique, aimed at gathering information from a representative sample of the population, as it is essentially cross-sectional, describing and interpreting the current situation. A total of 768 rural women respondents were sampled across the rural areas of the Niger Delta region in Nigeria. Findings - The results from the use of a combined propensity score matching and logit model indicated that the meagre interventions of MOCs' CSR targeted at the empowerment of rural women in custodians of seed, food and traditional knowledge for climate change resilience recorded significant success in improving the role of women in agricultural production, especially in women involvement across value chains. Practical implications - This suggests that any increase in the MOCs' CSR targeted at increasing rural women's access to seed preservation facilities, food processing facilities, extension system that impact strong body of knowledge and expertise that can be used in climate change mitigation, disaster reduction and adaptation strategies, will enhance women's responsibilities in households and communities, stewards of natural and household resources, and will position them well to contribute to livelihood strategies adapted to changing environmental realities. Social implications - This implies that MOCs' GMoUs' policies and practices should enhance women's participation; value and recognise women's knowledge; and enable women, as well as men farmers to participate in decision-making process in agriculture, food production, land and governance; as women need to be acknowledged and supported, as the primary producers of food in the region, able to both cultivate healthy food and climate change resilience through small scale agro-ecological farming system. Originality/value - This research contributes to gender debate in agriculture from a CSR perspective in developing countries and rational for demands for social projects by host communities. It concludes that business has an obligation to help in solving problems of public concern.
Keywords: 330; Environmental justice; custodians of seed; climate change resilience; gender equality; corporate social responsibility; multinational oil companies; sub-Saharan Africa